Phytase enzyme and its remarkable effects on chicken health - Raja Danish Muner; Yanzhen Bi; Farhan Farooq; Ali Haider Saleem; Babar Maqbool; Ghulam Abbas (Emerging Trends in Personalized Medicines, 2024)
Phytase enzyme catalyzes the hydrolysis of Phytate to mono, di, tri, tetra and penta Phosphate of Myoinositol and Inorganic Phosphate. Cereals, legumes and oilseeds are the main ingredients of animal feed. Phytic acid or phytate is the chief storage form of phosphorus in the feed obtained from these plant sources. Phytate bound important mineral, metal ions and amino acids with it, and in this way it is anti-nutritional element. Simple stomach animals for example pigs, birds (including poultry), and fish cannot metabolize phytic acid phosphorus, because of the reason that they have very limited levels of phytic acid degrading enzyme activity in their digestive tracts. Thus, in order to meet the nutritional requirements in poultry and swine feed inorganic form of phosphate is added frequently in feed. Microbial action in soil and water can easily convert phytic acid into free phosphate and in this way phosphorus pollution will be resulted which includes eutrophication which can be defined as pollution due to excess of phosphate in water that promote excessive algal growth which in turn decrease concentration of oxygen in water. Phytase simply changes phytic acid into free phosphate by its hydrolysis. In this way it provides phosphorus for the body consumption of monogastric animals. In addition to it, phytase also provide amino acids, minerals and metal ions to simple stomach animals by releasing them from phytic acid. Phosphorus pollution causes eutrophication which may be defined as decrease in oxygen concentration and increase in growth of Algae which is very dangerous for aquatic life. Phytase enzyme reduces eutrophication (phosphorus pollution) by converting phytate or phytic acid into less phosphorylated and less toxic form.
Keywords: Phosphorous toxicity; Phytase; Phytic acid and Poultry